HUBUNGAN ANTARA TINGKAT PENGETAHUAN, STATUS EKONOMI DAN KEBIASAAN MEROKOK DENGAN KEJADIAN TUBERKULOSIS PARU PADA ORANG DEWASA DI WILAYAH KERJA PUSKESMAS TUAN-TUAN KABUPATEN KETAPANG KALIMANTAN BARAT - Setiarni, Sri Marisya; Sutomo, Adi Heru; Hariyono, Widodo (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2011)
Background: Lung tuberculosis still be the health public problem at developing countries whole the world. Indonesia occupies sequence to 3 in world in the tuberculosis case after Chinese and India. Lung tuberculosis is also one of health public problem in Kabupaten Ketapang especially in Puskesmas Tuan-Tuan region. Problem causing of lung tuberculosis disease in this Puskesmas Tuan-Tuan hardly multi factor like still low public economics social level, the height of smoking habit level and the lack of knowledge about lung tuberculosis. The aim of this research find out the relationship between knowledge level, economic status and smoking habit with lung tuberculosis case at adult in Puskesmas Tuan-Tuan Kabupaten Ketapang Kalimantan Barat region. Method: This research was observational research using cross sectional design. There was 84 respondent. Data analysis conduct by frequency distribution, bivariate analysis applies Chi Square and multivariate analysis with logistics regression. Result: Result of this research indicates that from the variable knowledge level, economic status and smoking habit show there are relationship with lung tuberculosis case at adult in Puskesmas Tuan-Tuan Ketapang region which are knowledge level (p=0,026; RR=1,857; CI: 1,062-3,446) and smoking habit (p=0,011; RR=2,407; CI: 1,118-5,186). From the result of multivariate analysis variable that is most dominant related lung tuberculosis case at adult in Puskesmas Tuan-Tuan Ketapang region is smoking habit with significant value 0,012. Conclusion: Statistically, there was relationship between knowledge level and smoking habit with lung tuberculosis case at adult in Puskesmas Tuan-Tuan Ketapang region. There is no relationship between economic status with lung tuberculosis case at adult in Puskesmas Tuan-Tuan Ketapang region. The most dominant variable that is related to lung tuberculosis case at adult in Puskesmas Tuan-Tuan Ketapang region is smoking habit. Keyword: knowledge, economics status, smoking habit, lung tuberculosis at adult.